On psychological issues in math problems - Iosifovich Abramson, Yakov (Obutchénie. Revista de Didática e Psicologia Pedagógica, 2024)
Some psychological data based on results returning back from solving math problems which include psychological component such as self-restriction is sometimes irrelevant due to different reasons. Sometimes the possible error in great deal is caused by ill posed question and sometimes, especially regarding preschoolers and elementary school students it is mixed with their insufficient proficiency in operating with math concepts pertaining to the problem. In the article are also offered samples of fixing these issues by introducing set of questions preceding statement of the question.